Decomposition of co-worker wage gains - István Boza; Virág Ilyés (IZA Journal of Labor Economics, 2020)
We address the presence, magnitude, and composition of wage gains related to former co-workers and discuss the mechanisms that could explain their existence. Using Hungarian linked employer-employee administrative data and proxying actual co-workership with overlapping work histories, we show that the overall wage gain attributable to former co-workers consists of multiple elements: a contact-specific, an individual-specific, a firm-specific and a match-specific component. Former co-workers, besides the direct effect of their presence, may funnel individuals into high-paying firms, enhance the sorting of good quality workers into firms, and may contribute to the creation of better employer-employee matches. By introducing and applying a wage-decomposition technique, we demonstrate that there are non-negligible differences between linked and market hires in all empirically separable wage elements. By focusing on specific scenarios, we provide additional empirical evidence in favor of employee referral and information transmission as the main drivers of co-worker gains.
Keywords: J31; J64; M54; Z13; 330; co-worker network; wage decomposition; employee referral; match quality; information transmission; fixed effects; linked employer-employee data